2018
DOI: 10.1177/1352458517737372
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids and susceptibility to multiple sclerosis

Abstract: Dietary SCFAs constitute interesting candidates as safe and potent add-on therapy in the immunomodulatory treatment armamentarium for relapsing-remitting MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Propionate has been shown to function in inhibiting the biosynthesis of hepatic cholesterol, regulating food intake and obesity, and inducing hypophagia, which are related to metabolism and energy homeostasis 34,35 . Propionate also lowers lipogenesis and carcinogenesis risk, protects from hypertensive cardiovascular damage, and improves multiple sclerosis [36][37][38] . However, it is likely that the health-promoting effects of propionate are less studied than those of butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…Propionate has been shown to function in inhibiting the biosynthesis of hepatic cholesterol, regulating food intake and obesity, and inducing hypophagia, which are related to metabolism and energy homeostasis 34,35 . Propionate also lowers lipogenesis and carcinogenesis risk, protects from hypertensive cardiovascular damage, and improves multiple sclerosis [36][37][38] . However, it is likely that the health-promoting effects of propionate are less studied than those of butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple Sclerosis (MS) is an inflammatory disease of the central nervous system, leading to demyelination and formation of focal lesions with lymphocyte infiltration [334]. An autoimmune basis of MS depends on the imbalance between pro-inflammatory and anti-inflammatory mechanisms [335]. Animal model of experimental EAE has noted the beneficial effects of FAs mediated by shifting macrophage polarization from an M1-like inflammatory phenotype to an anti-inflammatory M2-like phenotype, which in turn prevents de-myelinization, promotes neuroprotection and re-myelinization [306].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Already in the 1950s, Swank et al observed that people who consumed less animal fat had lower rates of MS [ 7 ]. Studies investigating an MS animal model revealed harmful as well as beneficial effects of saturated fats, depending on their aliphatic chain length [ 8 ].…”
Section: Introductionmentioning
confidence: 99%